Influence of Physical Activity on Reduction of Delayed Onset Muscle Soreness - Jakub Grzegorz Adamczyk; Dariusz Białoszewski; Dariusz Boguszewski; Beata Oko; Sylwia Szkoda (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
The purpose of this study was to determine if physical activity of different intensity has an effect on reduction of delayed onset muscle soreness. Eighty women divided into two groups participated in the study. Subjects from Group 1 participated in the training of upper libs, whereas subjects from group 2 – in the training of lower limbs. Tests of power of upper limbs – the active overhang on the bar (Gr. 1) and power of lower limbs – the vertical jump test (Gr. 2), visual analog scale of pain (VAS) and the International Physical Activity Questionnaire (IPAQ) were used as investigative tools. The majority of studied women were characterized by the high level of physical activity. Physical activity level had strong positive correlation (r = 0.54; p < 0.001) with the reduction of pain. Taking into account the partition according to the kind of physical activity, there was observed some significant correlation between the diminution of delayed onset muscle soreness and the level of moderate activity and walking (relocating). Physical activity level positively correlated with the reduction of delayed onset muscle soreness. Moderate physical activity and walking proved to be the most beneficial from the reduction of delayed onset muscle soreness point of view.